Pengaruh Perubahan Sosial dan Modernisasi terhadap Pergeseran Perilaku Masyarakat di Era Globalisasi - Ina Fitriani; Salsabila Aura Auliyah; Sabilla Efitha Dewi; Delis Noni Herliani; Revan Tri Anggara; Yesi Yohana Silaban (Asosiasi Riset Ilmu Pendidikan Indonesia, 2026)
This study examines the influence of social change and modernization on the shifting behavior of society in the era of globalization. Globalization, accelerated by advances in information and communication technology, has fundamentally transformed social interaction patterns, value systems, and ways of life, including in Indonesia. This research employed a library research method with a descriptive qualitative approach, in which secondary data were collected from scientific journals, books, proceedings, and relevant academic documents, and subsequently analyzed using content analysis techniques. The findings indicate that modernization drives society toward more rational, open, and adaptive ways of thinking, while simultaneously enhancing civic awareness and participation in digital public spaces. However, modernization also presents significant challenges, including rising individualism, the weakening of conventional social solidarity such as mutual cooperation (gotong royong), and increased public vulnerability to the spread of misinformation due to low levels of digital literacy. Social media literacy is proven to be a critical factor in shaping critical and responsible civic behavior. The study concludes that strengthening digital literacy and sustained civic education are essential to enable society to harness the benefits of globalization productively without losing cultural identity and local social values.